Matheurísticas para o problema de custo de disponibilidade de recursos com múltiplos modos - Procópio, Lettiery D’Lamare Portela (2016)
This paper discribes the construction of two Matheuristics based on Genetic Algorithm and Particle Swarm Optimization in order to solve the Availability of Cost Problem Resources with Multi-Modes. Inspired by the need to balance the use of renawable resources with the total time (makespan), by scheduling the activities with its various implementations executions modes present in the project. Tests show the effectiveness in te use of mathematical programming adapted to the Genetic Algorithm.